Augustine's Confessions: A Biography. By Garry Wills - Barrett, Matthew (The journal of theological studies, 2011)
Though it is debatable, it is unlikely that there is a figure in church history who has been written on more than St Augustine of Hippo. One might assume that with the arrival of the twenty-first century no stone has been left unturned. But this is not the case. As studies continue to be written on Augustine, one lesson that should be evident to all is that the sheer depth of the writings Augustine left behind has left scholars busy for an eternity. Perhaps the work of Augustine that has received the most attention is his Confessions. Gary Wills demonstrates that we still have much to learn about Augustine., Wills takes the reader on a journey through the Confessions, opening one door after another, revealing aspects of Augustine's thought sometimes overlooked.